# Integration by Substitution Formula

Integration of substitution is also known as U – Substitution, this method helps in solving the process of integration function.

When a function cannot be integrated directly, then this process is used. To integration by substitution is used in the following steps:

- A new variable is to be chosen, let’s name t “x”
- The value of dx is to is to be determined.
- Substitution is done
- Integral function is to be integrated
- Initial variable x, to be returned.

The standard formula for integration is given as:

\[\large \int f(ax+b)dx=\frac{1}{a}\varphi (ax+b)+c\]

\[\large \int f\left(x^{n}\right)x^{n-1}dx=\frac{1}{n}\phi \left(x^{n}\right)+c\]

\[\large \int \frac{{f}'(x)}{f(x)}dx=log\:f(x)+c\]

Solved Examples

**Question: **Find the integration using the substitution formula: $\int \frac{(3+ln+2x)^{3}}{x}dx$

**Solution**

Let *u* = 3 + *ln* 2*x
*We can expand out the log term on the right hand side as: 3 +

*ln*2

*x*= 3 +

*ln*2 +

*ln x*

The first 2 terms on the right are constants (whose derivative equals zero) and the derivative of the natural log of* x* is $\frac{1}{x}$ .

Then:

$du=\frac{1}{x}dx$

$\int \frac{(3+ln\; 2x)^{3}}{x}dx= \int u^{3}du$

$=\frac{u^{4}}{4}+k$

$=\frac{(3+ln\:2x)^{4}}{4}+k$